STAD Type Cooperative Learning Model in Learning Understanding Abilities in MTs Nurul Islam Lumajang - Rofiatus Sholeha; muassomah muassomah (Abjadia, 2021)
This study aims to explain the application of STAD type cooperative learning in Arabic learning and reveal student’s perspectives on the applications of STAD type cooperative learning. This study used a qualitative descriptive approach, data was collected through observation, interviews, and student evaluation test results. This research was conducted by students of class VII MTs Nurul Islam. In this study, it can be seen the application of the STAD method in Arabic learning is carried out through five stages, namely presentation of material, group division, procurement of individual test, calculation of scores and awarding. With the application of the method, it can be foster student’s enthusiasm in learning Arabic, especially in reading comprehension skills. This research suggest that research is similar to multi-site, thereby producing veried and varied data and information by comparing several schools.